2011
DOI: 10.1371/journal.pone.0026153
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine Attenuates the Decreases in TrkB Protein Levels and the Anxiety/Depression-Like Behaviors in Mice Induced by Corticosterone Treatment

Abstract: ObjectiveStress and glucocorticoid hormones, which are released into the circulation following stressful experiences, have been shown to contribute significantly to the manifestation of anxiety-like behaviors observed in many neuropsychiatric disorders. Brain-derived neurotrophic factor (BDNF) signaling through its receptor TrkB plays an important role in stress-mediated changes in structural as well as functional neuroplasticity. Studies designed to elucidate the mechanisms whereby TrkB signaling is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 34 publications
4
45
4
Order By: Relevance
“…However, there were no significant changes in frontal cortex and hippocampal TrkB mRNA levels after long-term corticosterone or HCE treatment. The results indicated that long-term corticosterone affected the rate of TrkB protein synthesis or degradation but not TrkB mRNA, which was partly consistent with the previous study by Kutiyanawalla et al (2011). As a result, these data suggest HCE-induced antidepressant-like effect is likely through modulation of the BDNF-TrkB neurotrophic signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, there were no significant changes in frontal cortex and hippocampal TrkB mRNA levels after long-term corticosterone or HCE treatment. The results indicated that long-term corticosterone affected the rate of TrkB protein synthesis or degradation but not TrkB mRNA, which was partly consistent with the previous study by Kutiyanawalla et al (2011). As a result, these data suggest HCE-induced antidepressant-like effect is likely through modulation of the BDNF-TrkB neurotrophic signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical study demonstrates that depression is associated with reduced brain BDNF and its receptor (TrkB) levels and that the reductions can be restored up to the normal value by antidepressant treatment (Thompson et al, 2011). Animal studies have also demonstrated clear evidence that BDNF signaling through TrkB is involved in the mechanisms of action of antidepressant agents (Wang et al, 2010;Kutiyanawalla et al, 2011). BDNF and TrkB levels can therefore be useful markers for antidepressant-like response.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic corticosterone treatment has been shown to induce a depressive-like phenotype and a decrease in TrkB protein levels in mouse PFC 9 . We did not find any significant change in fluid consumption rate in mice following corticosterone administration for 7 weeks ( Supplementary Fig.…”
Section: Glucocorticoid Receptor Mediates Stress-induced Increase In mentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF), one of the important neurotrophic factors, has also been implicated in the pathophysiology of major depression and the mechanism of antidepressant treatment (Duman and Voleti, 2012;Hayley and Anisman, 2013). A growing number of studies have demonstrated clear evidence that BDNF signaling through tropomyosin-related kinase B (TrkB) is involved in the mechanisms of antidepressants in animal models (Kutiyanawalla et al, 2011;Yi et al, 2014a), and clinical study also demonstrates that depression is associated with reduced brain BDNF and its receptor, TrkB levels and that the reductions can be reversed to the normal value with antidepressant treatment (Thompson Ray et al, 2011).…”
mentioning
confidence: 99%